2002
DOI: 10.1120/jacmp.v3i4.2553
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of monitor unit calculations performed with a 3D computerized planning system and independent “hand” calculations: Results of three years clinical experience

Abstract: A comparison of the monitor unit calculations of a commercial 3D computerized treatment planning system (TPS) with “hand” calculations from lookup tables was made for a large number of clinical cases (greater than 13 500 treatment fields). Differences were analyzed by treatment site for prostate, rectum, cranium, and breast. The 3D TPS monitor unit calculation was systematically higher than the “hand” calculation by an amount that depended on the complexity of the treatment geometry. For simple geometries the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Independent verification of the treatment planning system (TPS) calculations is an essential part of the quality assurance (QA) process in radiation therapy. This verification is traditionally based on manual monitor unit (MU) calculation methods for 3D conformal radiotherapy (3D CRT) treatments 3 , 4 , 5 , 6 , 7 . The complexity present in the modulated treatments requires an introduction of a comprehensive quality assurance program aimed at its implementation (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Independent verification of the treatment planning system (TPS) calculations is an essential part of the quality assurance (QA) process in radiation therapy. This verification is traditionally based on manual monitor unit (MU) calculation methods for 3D conformal radiotherapy (3D CRT) treatments 3 , 4 , 5 , 6 , 7 . The complexity present in the modulated treatments requires an introduction of a comprehensive quality assurance program aimed at its implementation (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Jackson et al 23 . confirmed that the differences in MU between manual and TPS calculations for breast radiotherapy increase when these calculations require OAR(r) corrections, and compared 6 MV and Cobalt beams (the OAR correction is neglected for Co‐60) under similar conditions while neglecting influencing factors such as tissue heterogeneities in both calculations.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, several mathematical formulas were developed to improve the accuracy of calculations for asymmetric fields based on the GESF concept, 12,18–21 the simplest of which is the area‐perimeter ratio 22 . According to these formulas, in order to calculate the S cp for asymmetric fields, the S c and S p of their GESF can be used 3,23–26 …”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent accidents in radiotherapy, the monitor unit recalculations are a prerequisite component of quality assurance (QA) in radiation therapy. Because errors and large uncertainties in dose calculations reduce the quality of a treatment, MU recalculations have been recommended as a routine quality assurance (QA) procedure when verifying individual treatment plans [1]. Even though the validity of the calculation algorithms can be passed during the commissioning of a TPS, verification of the monitor units calculated by the TPS is typically performed using a ''hand'' calculation based all of standard beam data.…”
Section: Introductionmentioning
confidence: 99%